2016
DOI: 10.1002/nur.21733
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nurse‐Physician Collaboration on Job Satisfaction, Team Commitment, and Turnover Intention in Nurses

Abstract: Voluntary turnover in nursing can lead to nursing shortages that affect both individuals and the entire hospital unit. We investigated the relationship between group- and individual-level variables by examining the association of nurses' job satisfaction and team commitment at the individual level, and nurse-physician collaboration at the group level, with individuals' intention to leave the unit at the individual level. A self-report questionnaire was administered to 1,024 nurses on 72 units in 3 Italian hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 91 publications
(71 reference statements)
5
70
0
8
Order By: Relevance
“…Firstly, researchers have concluded that participating in hospital affairs could improve registered nurses' job satisfaction (Dekeyser & Toren, 2014), and we found that hospital affair participation could enhance nurses' career success. Secondly, researchers have found that in clinical work, active cooperation could improve job satisfaction (Galletta, Portoghese, Carta, D'Aloja, & Campagna, 2016), which in an indirect way confirmed our finding that collegial nurse-physician relations positively affected career success. Meanwhile, a previous study showed that adequate staffing and resources could effectively improve nurses' job satisfaction (Squires et al, 2015), and we expanded job satisfaction to career success by showing that staffing and resource adequacy positively affected nurses' career success.…”
Section: Work Environment and Career Successsupporting
confidence: 87%
“…Firstly, researchers have concluded that participating in hospital affairs could improve registered nurses' job satisfaction (Dekeyser & Toren, 2014), and we found that hospital affair participation could enhance nurses' career success. Secondly, researchers have found that in clinical work, active cooperation could improve job satisfaction (Galletta, Portoghese, Carta, D'Aloja, & Campagna, 2016), which in an indirect way confirmed our finding that collegial nurse-physician relations positively affected career success. Meanwhile, a previous study showed that adequate staffing and resources could effectively improve nurses' job satisfaction (Squires et al, 2015), and we expanded job satisfaction to career success by showing that staffing and resource adequacy positively affected nurses' career success.…”
Section: Work Environment and Career Successsupporting
confidence: 87%
“…Conversely, poor nurse – nurse relationships may increase nurse turnover (Tuckett, Winters‐Chang, Bogossian, & Wood, ). These findings are consistent with those of Galleta, Portoghese, Carta, D'Aloja, and Campagna (), whose results suggest that nurses who have higher levels of job satisfaction and experience positive collaboration with physicians are more committed to their teams.…”
Section: Introductionsupporting
confidence: 91%
“…As measured in this study, stressors included job risks, impact of patient care, inadequate preparation for job demands, lack of support, interpersonal relationships and hospital policy/demands. Possible strategies to decrease these job‐related stressors included provision of training to prepare nurses for job demands (Mosadeghrad, ), use of information systems or technology to increase job efficiency (Buntin, Burke, Hoaglin, & Blumenthal, ), increasing autonomy in developing nursing skills/knowledge and decision making in nursing care (Papathanassoglou et al., ) and promoting positive nurse‐physician collaboration through mutual respect, open and affective communication and interprofessional simulation training (Galletta, Portoghese, Carta, D'Aloja, & Campagna, ; Liaw, Siau, Zhou, & Lau, ). These changes could benefit both individuals and the organization (Allan et al., ; Happell et al., ; Trybou et al., ).…”
Section: Discussionmentioning
confidence: 99%